Forestry Education and Training in Indian Council of Forestry Research and Education - Singh, Omkar; Dogra, Rakesh Kumar; Negi, Anil (Indian Forester, 2013)
The Indian Council of Forestry Research and Education, Dehradun, being an umbrella organization under the Ministry, is actively engaged in forestry research and knowledge dissemination through its eight research institutes and four advanced centers all over India. The paper describes the financial assistance by ICFRE to universities, initiative for accreditation of forestry Institutions and courses, training at National and International level to the scientific/managerial cadre/research support staff under HRD Plan and participation of officers/scientists in seminars/workshop/conferences, policy on human resource development in ICFRE, gap analysis in forestry education and strategies for forestry education in India. The objectives of Forest Research Institute Deemed University (FRIDU) and recognized research centers of FRI Deemed University are also described.